On Neuroeducation: Why and How to Improve Neuroscientific Literacy in Educational Professionals - Jolles, Jelle; Jolles, Dietsje D. (Frontiers in Psychology, 2021)
New findings from the neurosciences have received much interest for use in the applied field of education. For the past 15 years, Neuroeducation and ‘neuroscientific literacy’ and the application of neuroscience knowledge were seen to have promise, but there is presently some lack of progress. The present paper states that this is due to several factors. Neuromyths are still prevalent, and there is a confusion of tongues between the many neurosciplines and the domains of educational and behavioral sciences. Second, a focus upon cognitive neuroimaging research has yielded findings which are scientifically relevant, but can not be used for direct application in the classroom. A third factor pertains to the emphasis which has been on didactics and teaching, whereas the promise of neuroeducation for the teacher may lie more on pedagogical inspiration and support. This article states that the most important knowledge and insights have to do with the notion of brain plasticity; the vision that the organization of our brain has the goal to help us select and process information, and to help the indivial to adapt to an ever changing environment. The paper describes how brain maturation and neuropsychological development extend through the important period of adolescence and emergent adulthood. Over this long period, there is a major development of the Executive Functions (EF’s) that are essential for both cognitive learning, social behavior and emotional processing and, eventually, personal growth. The EF’s provide tools which could be relevant for the educational professional. The paper eventually describes the ‘neuroscientific literacy’ which the educational professional should have, and the authors formulate a proposal for four themes of neuroscience content ‘that every teacher should know’. As to approach, it is stated that attempts directed at improving neuroscientific literacy are a transdiciplinary undertaking. Teacher trainers, experts from the neuroscience fields but also behavioral scientists from applied fields (notable applied neuropsychologists) are needed for the educational innovations needed.